Two large benign branch-duct gastric-type intraductal papillary mucinous neoplasms of the pancreas with positive GNAS mutations: A question of when or using which technique to operate? - Tampakis, Athanasios (Pancreas, 2016)
An abstract is unavailable.
Gesehen am 29.10.2019